A Low-Cost RSSI-Based Localization System for Wildlife Tracking - Hartmann, Markus; Nowak, Thorsten; Patino-Studencki, Lucila; Robert, Jörg; Heuberger, Albert; Thielecke, Jörn (IOP Conference Series: Materials Science and Engineering, 2016)
This paper presents a low-cost localization system for the high-resolution tracking of bats. The system bases on a ground network consisting of multiple low-cost receiver stations, and ultra-lightweight transmitters mounted on the bats. A main challenge of the received signal strength based localization is the limited dynamic range of the employed low-cost receivers. This challenge is solved using an efficient 2-stage differential correlation concept. It significantly improves the dynamic wrt. conventional power detection methods. In addition, this concept requires low processing power and is robust wrt. frequency offsets. Finally, this paper presents a performance evaluation employing reference measurements recorded in the rain forest of Panama.    </